Engineered Sustainable Mxene-PVA Hydrogel as an Inspiring Co-Delivery Carrier for Targeting Solid Tumors - Elham Ghazizadeh; Mahya Sadeghi; Hans-Peter Deigner; Ali Neshastehriz (Pharmaceutics, 2025)
Background: Solid tumors have long presented a significant challenge in the field of oncology due to their ability to develop resistance to multiple drugs, known as multidrug resistance (MDR). This phenomenon often leads to treatment failure and poor patient outcomes. In recent years, researchers have been exploring innovative approaches to combat MDR, including the use of hydrogels for localized drug delivery. Methods: Through the biological crosslinking of an MB-smDNA-MB agent to form a pH sensitive hydrogel matrix, we introduce the injection coating of a novel PVA-MB-smDNA-MB-Mxene (PMSDMM) carrier for Adriamycin (a potent chemotherapy drug) and miR-375 (as tumor-suppressive microRNA) delivery. Results: We aimed to enhance the effectiveness of drug delivery to solid tumors while minimizing systemic toxicity via the pH-sensitive characteristics of methylene blue at the end of smDNA as a dsDNA biological crosslinking agent, i.e., anti-miR-375 PMSDMM ADR. Our hydrogel was shown to improve the release of the drug in the acid tumor environment. In the first 24 h, the cumulative release rate was higher at pH = 5.5 than at pH = 7.4. Conclusions: We show that this DNA bio-inspired PMSDMM hydrogel has potential in hydrogel injection applications for tumor suppression and tissue regeneration after the surgical resection of tumors.